Training in exercises for pelvic floor muscles of patients with an urinary incontinence after radical prostatectomy - P. V. Glybochko; Yu. G. Alyaev; A. Z. Vinarov; L. M. Rapoport; E. A. Bezrukov; Yu. L. Demidko; L. S. Demidko (Андрология и генитальная хирургия, 2014)
Training of muscles of a pelvic bottom under control of biofeedback is applied at 87 patients with an urinary incontinence after a radical prostatectomy. Biofeedback increases management and control of a pelvic floor. At good ability of management of muscles of a pelvic floor the median of restoration was 4 months. Without opportunity of management of muscles of pelvic floor restoration was 9.4 months.